Divergent Regulation of OCT and MATE Drug Transporters by Cadmium Exposure - Yang, Hong (Pharmaceutics, 2021)
Coordinated transcellular transport by the uptake via organic cation transporters (OCTs) in concert with the efflux via multidrug and toxin extrusion proteins (MATEs) is an essential system for hepatic and renal drug disposition. Despite their clinical importance, the regulation of OCTs and MATEs remains poorly characterized. It has been reported that cadmium (Cd(2+)) increase the activities of OCTs while being a substrate of MATEs. Here, we found that human (h) OCT2 protein, as compared with hMATE1, was more active in trafficking between the plasma membrane and cytoplasmic storage pool. Cd(2+) exposure could significantly enhance the translocation of hOCT2 and hOCT1, but not hMATE1, to the plasma membrane. We further identified that candesartan, a widely prescribed angiotensin II receptor blocker, behaved similarly toward OCT2 and MATE1 as Cd(2+) did. Importantly, Cd(2+) and candesartan treatments could lead to an enhanced accumulation of metformin, which is a well-characterized substrate of OCTs/MATEs, in mouse kidney and liver, respectively. Altogether, our studies have uncovered possible divergent regulation of OCTs and MATEs by certain xenobiotics, such as Cd(2+) and candesartan due to the different cellular trafficking of these two families of transporter proteins, which might significantly affect drug disposition in the liver and kidney.